Marchesinia principensis (Marchantiophyta, Lejeuneaceae), a new liverwort species from Príncipe, West Africa - Müller, Frank; Shevock, James R. (Phytotaxa, 2018)
A new species, Marchesinia principensis (Marchantiophyta, Lejeuneaceae), is described and illustrated from Príncipe, Republic of São Tomé and Príncipe, West Africa. It was discovered in cloud-mist hardwood forests at elevations of 500–690 m. This new species most closely resembles Marchesinia excavata, but differs in the broad reniform underleaves, 5–6 × as wide as the stem, >2 × as wide as long, the narrow angle (< 90°) that the ventral margin of the lobe makes with the keel, and the usually flat ventral margin of the lobe. M. principensis is, furthermore, a more robust plant than M. excavata.